Development of a calcified odontogenic hamartoma following avulsion of a permanent central incisor. Issue 3 (30th October 2019) - Procópio, Stefânia Werneck; Matos, Hiorran Coelho de Almeida; de Oliveira, Pedro Lima Emmerich; de Andrade, Bruno Augusto Benevenuto; Agostini, Michelle; Esteves, Jonatas Caldeira; de Campos, Paulo Ricardo Barros; de Souza, Margareth Maria Gomes; Maia, Lucianne Cople
Abstract: The avulsion of a permanent immature tooth is a serious condition and a real emergency in dentistry. The management of a traumatized avulsed tooth is always a challenge to the clinician. This case report concerns the development of a calcified odontogenic hamartoma after the avulsion of an immature central incisor in an eight‐year‐old female. The patient presented for the treatment four months after the avulsion. Her intraoral examination showed complete healing of the area but an atypical appearance of the alveolar area of the missing tooth was observed in the periapical radiograph. A new radiographic scan performed six months later revealed the formation of a radiopaque irregular structure at the cervical level of the alveolar ridge at the site of the missing tooth. Surgical removal was performed, and the histopathological examination revealed a hamartomatous proliferation of odontogenic tissue with calcification. After healing, the lateral incisor was orthodontically moved mesially and restored to resemble the central incisor. An orthodontic device was installed to improve function and aesthetics of the patient.